More than a paycheck: How non-financial incentives shape employee motivation in public administration - Irwan, Andi; Anwar, Vebby; Zaitun, Cakra (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
This study examines how non-monetary rewards affect worker motivation in Indonesia’s public sector, highlighting the moderating influence of leadership style and the mediating function of perceived organizational support (POS). Partial Least Squares Structural Equation Modelling (PLS-SEM) and survey data from 357 public sector workers were used to confirm that work-life balance, career advancement, job enrichment, and recognition significantly increase motivation, with career development having the most impact. POS mediates these ties, and their influence is increased by transformational leadership. These observations, which emphasize the value of organized career development, successful recognition programs, and leadership training, add to the body of knowledge in human resource management and provide valuable suggestions for legislators. Public service performance can be improved, and staff motivation can be raised by bolstering organizational support and encouraging leadership involvement.